(untitled) (Papeles, 2023)
Introduction: The scientific-technical development, at present, requires profound changes in higher education, so the teaching-learning process needs a holistic vision to favor the integral formation of university students, however, in educational practice they have been detected. insufficiencies since there is a tendency towards a disciplinary approach; for which the investigative work has focused on the following question: How to favor the integral formation of university students through a holistic vision in the teaching-learning process? Consequently, the objective has been set: to socialize a didactic strategy, made up of integrating teaching tasks, that favor the treatment of a holistic vision of the teaching-learning process to contribute to the integral formation of students. Methodology: The research has followed a qualitative perspective, carrying out a descriptive study on the essential features of the object, through the use of methods of the theoretical and empirical level, necessary to prepare the theoretical framework, analyze the current state of the object, elaborate the solution proposal to the problem and the conclusions. Results and discussion: The results obtained show difficulties in establishing links between the content studied and previous and subsequent knowledge, its generalizing analysis is not encouraged, it is fragmented into its different manifestations, which does not favor its global understanding. Conclusions: It is concluded that it is necessary to assume a holistic vision in the teaching-learning process, through integrating teaching tasks, which enriches the process, establishing deep relationships and interrelationships between different fields of knowledge, providing solidity to student learning.